Counting better? An Examination of the Impact of Quantitative Method Teaching on Undergraduate Social Science Student’s Statistical Anxiety and Confidence to complete Statistical Tasks - Marty Chamberlain (Active Learning in Higher Education, 2015)
This article reports the results of research concerned with students’ statistical anxiety and confidence to both complete and learn to complete statistical tasks. Data were collected at the beginning and end of a quantitative method statistics module. Students recognised the value of numeracy skills but felt they were not necessarily relevant for graduate employability and preferred to study with words rather than numbers. A significant reduction in anxiety and increase in confidence to complete statistical tasks were found. Students seemed to feel more confident about doing and learning less complex procedures. Results reinforce the need to provide students with additional mathematical and statistical support outside of quantitative method courses as well as that numeric learning materials and study tasks need to be embedded across the curriculum within substantive disciplinary modules. The design of numeric study tasks needs to be carefully considered to ease the transition for students from simple to more complex statistical procedures while simultaneously reinforcing the importance of numeracy skills for examining substantive disciplinary topics and promoting graduate employability